Generic Search Plans for Matching Advanced Graph Patterns - Horváth, Ákos; Varró, Gergely; Varró, Dániel (Electronic Communications of the EASST, 2007)
In the current paper, we present search plans which can guide pattern matching for advanced graph patterns with edge identities, containment constraints, type variables, negative application conditions, attribute conditions, and injectivity constraints. Based on a generic search graph representation, all search plan operations (e.g. checking the existence of an edge, or extending a matching candidate by navigating along an edge) are uniformly represented as special predicates with heuristically assigned costs. Finally, an executable search plan is defined as an appropriate ordering of these predicates. As a main consequence, attribute, injectivity, and negative application conditions can be checked early (but not unnecessarily early) in the pattern matching process to cut off infeasible matching candidates at the right time.